Perancangan Mobile Application untuk Startup Montirkeliling.com dengan Metode Design Sprint - Ashshiddiqy, Nur Rohman; Astawa, Ni Luh Putu Ning Septyarini Putri; Nirmala, Bagus Putu Wahyu; Paramitha, A.A Istri Ita (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2021)
The development of technology today is very influential in all fields. Including in the business field, information technology is very influential, for example, today many businesses depend on websites orapplications mobile in carrying out their business processes such as promotion and ordering of products or services offered. One example of a business that can use this business method is call vehicle service services. The problem found from initial observations is that online service orders are still very manual, namely still using thefeature chat (WhatsApp), which makes potential customers and mechanics find it difficult to find a mechanic or the location of the customer. Based on these problems, the researchers designed the user interface for the Montirkeliling.com application based on aapplication mobile that can help prospective customers and mechanics. The design method used is themethod sprint design. This method is a design method developed by Google Inc. which aims to solve problems by involving users through making, prototyping, designing and testing ideas quickly for 5 working days consisting of five stages. The result of this research is the design of the Montirkeliling.com User Interface which has been tested on prospective users using the System Usability Scale (SUS). The average SUS score obtained is 83.5, which is included in Grade B.Keywords—Planning, Startup Montirkeliling.com, Metode Design Sprint